Swamp Thing the Bronze Age omnibus - Wein, Len 1948-2017; Pasko, Martin; Micheline, David 1948- (DC Universe Rebirth, 2017)
Volume 1: "From his first appearance in HOUSE OF SECRETS from creators Len Wein and Bernie Wrightson, the adventures of Swamp Thing have been some of the most terrifying and epic tales in DC Universe lore. These stories gave birth to such classic characters as Dr. Anton Arcane, the Un-Men, Abigail Arcane and more! This giant compendium edition collects all the Bronze Age stories featuring Alec Holland's nightmarish alter ego! This oversize omnibus collection features the talents of industry legends Gerry Conway, David Michelinie, Steve Englehart, Martin Pasko and more!"...